ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN TAHUNAN PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Agung Widiantara; Ratna Sari Dewi; Murni Dahlena (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2022)
The purpose of this study was to determine whether partially or simultaneously the effect of leverage, liquidity, profitability, company size and company age on the completeness of the disclosure of the annual report of food and beverage companies listed on the Indonesia Stock Exchange (IDX). The sample in this study amounted to 29 companies consisting of 3 periods, namely 2018 to 2020, so the number of panel data processed in this study was 87 data. The data collection technique used was literature study and documentation. Data processing using SPSS Version 20.0 for windows. Data analysis techniques used are classical assumptions, multiple linear regression, and hypotheses. The results obtained (1) leverage does not affect the completeness of the disclosure of the annual report of food and beverages companies listed on the Indonesia Stock Exchange (IDX), (2) liquidity does not affect the completeness of the disclosure of the annual report of food and beverages companies listed on the Indonesia Stock Exchange. (IDX), (3) profitability does not affect the completeness of the disclosure of the annual report of food and beverages companies listed on the Indonesia Stock Exchange (IDX), (4) company size does not affect the completeness of the disclosure of the annual reports of food and beverages companies listed on the Stock Exchange. Indonesia (IDX), (5) Company age has a positive and significant effect on the completeness of the disclosure of the annual report of food and beverages companies listed on the Indonesia Stock Exchange (IDX), (6) simultaneously leverage, liquidity, profitability, company size, and company age positive and significant effect on k complete disclosure of the annual report of food and beverages companies listed on the Indonesia Stock Exchange (IDX). The influence of the independent variable on the dependent variable is 21.8%. While the remaining 78.2% of the dependent variable can be explained by other variables not discussed in this study